2017
DOI: 10.1111/nicc.12276
|View full text |Cite
|
Sign up to set email alerts
|

Effects of simulation education on oral care practices – a randomized controlled trial

Abstract: The need for regularly repeated educational sessions with theoretical training and practical exercises and direct feedback is evident. Certain aspects of oral care, such as prevention of microaspiration of oropharyngeal secretions and moistening of oral mucosa and lips, require more reinforcement than others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 27 publications
1
23
0
2
Order By: Relevance
“…There was a higher prevalence of evidence-based studies 6 (17), followed by level 2 (05), level 3 (04), level 7 (02) and level 1 (01). There is a growing number of scientific production related to the topic, with 16 articles published in the last three years (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) , making up 55% of the searches found in the selected period.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There was a higher prevalence of evidence-based studies 6 (17), followed by level 2 (05), level 3 (04), level 7 (02) and level 1 (01). There is a growing number of scientific production related to the topic, with 16 articles published in the last three years (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) , making up 55% of the searches found in the selected period.…”
Section: Resultsmentioning
confidence: 99%
“…It can be observed in Chart 2 that 34.5% of the studies are referenced to the use of simulation in education on care techniques of nursing activities, such as mechanical ventilation and invasive airway acquisition, cardiopulmonary resuscitation, oral hygiene and airway aspiration, hand hygiene and delirium identification in ICU patients (21)(22)(23)(24)(25)(26)(29)(30)(31)36) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[18] Comprehensive oral care programs that improve efficiency and efficacy should be carefully developed, implemented and regularly evaluated in order to ensure consistency and high quality of standardized care. [25] The survey conducted in India showed that additional education is necessary to increase awareness of the relationship between dental plaque and the patient's systemic conditions. [26] Oral care protocol In the present study, more than three quarters (76.6%) of participants reported that there was no mouth care protocol in ICU to guide oral care practice, and this was likely linked to the poor oral care performance.…”
Section: In-service Trainingmentioning
confidence: 99%
“…The effect of simulation education on critical care nurses' oral care practices was the subject of a randomized controlled trial by Jansson et al . (). The trial contained several quality design features, including transparent reporting of study progress in accordance with recognized standards.…”
mentioning
confidence: 97%